Inhibition Effects of 5-Amino-1,3,4-thiadiazole Derivatives on Carbonic Anhydrase Enzyme - VURAL, S.; BULBUL, M. (Asian Journal of Chemistry, 2010)
In this study, new carbonic anhydrase inhibitors's effects on bovine carbonic anhydrase enzyme, to resembling human carbonic anhydrase- II (hCA-II), as candidates for treatment of glaucoma were investigated. Therefore, carbonic anhydrase enzyme was purificated from bovine erythrocyte cells by the affinity column. The inhibition effects of 5-amino- 1,3,4-thiadiazole-2-sülfonamide (1), acetazolamide (2) and new synthesized amides (5, 6, 7) on this enzyme have been studied in vitro. The IC50 concentrations (the concentration of inhibitor producing a 50 % inhibition of bovine erythrocyte carbonic anhydrase activity) against hydratase activity values were 0.179, 0.758, 0.978 μM for bovine erythrocyte carbonic anhydrase. The IC50 values against esterase activity values were 0.225, 0.194 and 0.205 μM for this enzyme. The Ki values were observed 0.351, 0.208 and 0.232 μM for this enzyme. The comparison of new synthesized amides (5, 6, 7) to 1 and 2 indicated that the new synthesized compounds (5, 6, 7) inhibit carbonic anhydrase activity more effectively than parent compounds.